2016
DOI: 10.1002/ejhf.537
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of endogenous erythropoietin in long‐term outcome of patients with acute decompensated heart failure

Abstract: AimsAlthough previous reports suggest that an elevated endogenous erythropoietin (EPO) level is associated with worse clinical outcomes in chronic heart failure (HF) patients, the prognostic implication of EPO in patients with acute decompensated HF (ADHF) Methods and resultsWe examined 539 consecutive ADHF patients with EPO measurement on admission from our registry. During a median follow-up period of 329 days, a higher EPO level on admission was independently associated with worse clinical outcomes [haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
1
21
0
3
Order By: Relevance
“…The validation cohort for our study was the NaDEF study: an ongoing, prospective, single‐centre acute HF registry conducted at the National Cerebral and Cardiovascular Center in Osaka, Japan (West Japan), that began from January 2013. The objectives and detailed design are provided on the University Hospital Medical Information Network (UMIN000017024) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The validation cohort for our study was the NaDEF study: an ongoing, prospective, single‐centre acute HF registry conducted at the National Cerebral and Cardiovascular Center in Osaka, Japan (West Japan), that began from January 2013. The objectives and detailed design are provided on the University Hospital Medical Information Network (UMIN000017024) …”
Section: Methodsmentioning
confidence: 99%
“…The objectives and detailed design are provided on the University Hospital Medical Information Network (UMIN000017024). 16,17…”
Section: Study Populationmentioning
confidence: 99%
“…EPO levels were assessed at intervals of more than 72 h from the last injection of rHuEPO; therefore, the impact of rHuEPO might have been small. Several studies have reported an increased level of plasma EPO in patients with heart failure, which was correlated to a more severe outcome [10][11][12][13]. Meanwhile, female gender, inflammation, hyperphosphatemia, hyperglycemia, and dyslipidemia were identified as potential risk factors of microvascular dysfunction [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…However, there may be differences across countries due to differences in healthcare systems and ethnicities . Nagai et al . have applied five different prognostic models developed in the U.S. and Europe to HF patients prospectively enrolled in the UK and Japan.…”
Section: Patients' Outcomesmentioning
confidence: 99%